2013
DOI: 10.1002/bmc.2877
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new UPLC‐MSMS method for the determination of temozolomide in mice: application to plasma pharmacokinetics and brain distribution study

Abstract: A sensitive and accurate liquid chromatography method with mass spectrometry detection was developed and validated for the quantification of temozolomide in mouse plasma and brain. Theophyllin was used as the internal standard. A single-step protein precipitation was used for plasma and brain sample preparation. The method was validated with respect to selectivity, extraction recovery, linearity, intra- and inter-day precision and accuracy, limit of quantification and stability. The method has a limit of quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…This result was similar to the recovery reported by Kim et al, who found a recovery for TMZ in human plasma of ~47–50% to a concentration range of 0.1–20 mg/mL (Kim et al, ). Another previous study obtained a recovery between 40.7 and 55.5% for a 5.000 μg/mL concentration of TMZ in plasma and a recovery about 60% for 125–12.500 ng/g in brain (Goldwirt et al, ). In this context, the development of a method able to quantify low levels of TMZ and to recover high drug contents from biological samples is a key consideration in pharmaceutical development, taking into account that the previous described methodologies for TMZ quantification in biological samples employ a complex extraction method or result in low drug recovery.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This result was similar to the recovery reported by Kim et al, who found a recovery for TMZ in human plasma of ~47–50% to a concentration range of 0.1–20 mg/mL (Kim et al, ). Another previous study obtained a recovery between 40.7 and 55.5% for a 5.000 μg/mL concentration of TMZ in plasma and a recovery about 60% for 125–12.500 ng/g in brain (Goldwirt et al, ). In this context, the development of a method able to quantify low levels of TMZ and to recover high drug contents from biological samples is a key consideration in pharmaceutical development, taking into account that the previous described methodologies for TMZ quantification in biological samples employ a complex extraction method or result in low drug recovery.…”
Section: Introductionmentioning
confidence: 92%
“…Nevertheless, during pharmaceutical development, it is essential to use an adequate methodology for drug determination in analytical or bioanalytical assays, with an accurate quantification of the compounds of interest (Baptista, Oliveira, & Ferreira, ; Yazbi, Hassan, Khamis, Ragab, & Hamdy, ). Some methods, including high‐pressure liquid chromatography with ultraviolet (HPLC–UV) detection (Shen et al, ; Gilant, Kaza, Szlagowska, Serafin‐byczak, & Rudzki, ; Jain, Athawale, Bajaj, & Shrikhande, ), ultra‐performance liquid chromatography tandem mass spectrometry (UPLC–MS/MS) (Goldwirt, Zahr, Farinotti, & Fernandez, ) and liquid chromatography tandem mass spectrometry (LC–MS/MS) (Diez et al, ), have been reported for TMZ analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Few methods based on LC-UV [256][257][258][259][260][261] and LC-MS [262][263][264][265][266] were reported for the analysis of triazene compounds and procardazine in biological matrices. An LOQ of 0.5 ng mL −1 was achieved for the analysis of dacarbazine 266 and procarbazine 265 in plasma samples by LC-MS. Lower sensitivity (LOQ of 50 ng mL −1 ) was reached with LC-MS for the temozolomide assay in plasma.…”
Section: 233-237mentioning
confidence: 99%
“…An LOQ of 0.5 ng mL −1 was achieved for the analysis of dacarbazine 266 and procarbazine 265 in plasma samples by LC-MS. Lower sensitivity (LOQ of 50 ng mL −1 ) was reached with LC-MS for the temozolomide assay in plasma. 264 A micellar electrokinetic chromatography (MEKC) method has also been reported for the determination of temozolomide and its degradation products in water and serum. 267 The choice of the MEKC method was based on: (i) the absence of charge on temozolomide in neutral and acidic conditions; and (ii) its low stability in solution.…”
Section: 233-237mentioning
confidence: 99%
“…Whole brains were collected, rinsed with 0.9 % sodium chloride and directly frozen at -20°C in polyethylene tubes. Temozolomide levels in mice plasma and brains were measured using their respective assay procedures as previously published [24].…”
Section: Pharmacokinetics Studymentioning
confidence: 99%